An Alliance-led technical process resulted in two ministries adopting guidance for sustainable agriculture in Colombia´s fragile moorlands - Rivas, Juan Sebastián (2023)
In Colombia, the Alliance led a technical process to formulate the Inter-ministerial Resolution 249 of 2022. This is a public policy document of great importance for guiding the response to agricultural activities prohibited by the Law 1930 of 2018 but continue to be carried out in delimited moorlands, generating significant negative impacts on those ecosystems. This document requires public institutions working in these ecosystems to adjust their programs, projects and actions to comply with these new regulations. The benefits of the Technical document of guidelines for the design, training, and implementation of programs, plans, and projects for the conversion and substitution of agricultural activities in delimited moorlands that resulted in the Inter-ministerial Resolution 249 of 2022, are as follows: Protection of valuable ecosystems; Subsistence of those who live in and depend on these ecosystems; Reconciliation of environmental and productive positions; Collective construction.